SISTEM INFORMASI PENGARSIPAN DATA SURAT BERBASIS VISUAL STUDIO 2012 DAN MYSQL - Sri Tria Siska; Ramacos Fardela; hilda fenia (Ensiklopedia of Journal, 2022)
In the current era of globalization, the development of science and technology continues to advance rapidly. This encourages various changes that are very fast in terms of life and it is undeniable that these changes are felt in everyday life. One of the results of utilizing technological advances is the use of computers, which in the present and in the future will be very much needed, because it has been proven that computers are tools in completing human work accurately, effectively and efficiently. The research method uses observation and interview techniques to obtain information related to filing letters using a computerized system. Microsoft Visual Basic is a programming language that offers an Integrated Development Environment (IDE) that creates software programs based on the Microsoft Windows operating system using a programming model. MySQL (My Structure Query Language) or commonly read "mai-se-kuel" is a database creation program that is open source and runs on all platforms, both Windows and Linux. In addition, MySQL is also a program to access databases that can be used for applications with multiple users (Multi User).Keywords: Information System, Archiving, Mail Data, Visual Studio 2012 and MySql